2022
DOI: 10.21037/atm-22-1020
|View full text |Cite
|
Sign up to set email alerts
|

The choice of medical facility and associated factors among Chinese advanced colorectal cancer patients: a cross-sectional multi-center study

Abstract: Background: Colorectal cancer (CRC) poses a significant public health burden worldwide. The investigation of the choice of medical facility among CRC patients is helpful for understanding access to health services and improving quality of oncology services to optimize health outcomes. However, there are limited studies on the topic. The objective of this study was to investigate the choice of medical facility and its associated factors among advanced CRC patients.Methods: This cross-sectional multi-center stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The quali cations or expertise of medical service providers was an important determinant of patients' medical institution choice (32,36). Additionally, the subgroup analysis further revealed that patients in the female group and the non-elderly group showed a preference for seeking inpatient treatment in large provincial and municipal tertiary hospitals (35).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The quali cations or expertise of medical service providers was an important determinant of patients' medical institution choice (32,36). Additionally, the subgroup analysis further revealed that patients in the female group and the non-elderly group showed a preference for seeking inpatient treatment in large provincial and municipal tertiary hospitals (35).…”
Section: Discussionmentioning
confidence: 96%
“…Institutional scale was the second most important attribute of patients' preference for inpatient institutions. Since many tertiary hospitals in China's provinces and cities were medical institutions with better technical capability and e ciency (35), it is not hard to understand that MCC patients were more willing to go to large provincial and municipal tertiary hospitals to obtain high-quality medical services. The quali cations or expertise of medical service providers was an important determinant of patients' medical institution choice (32,36).…”
Section: Discussionmentioning
confidence: 99%